Notes on "visive spirits", poetry and theory of knowledge from a poem by Leopoldo María Panero - García Valdés, Olvido (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper proposes a reading of the poem “Ma mère” by Leopoldo María Panero from an intertext by Guido Cavalcanti that refers to the Neoplatonic philosophy of love. This philosophy favors the sense of sight, which Panero relates to the concept of "fascination", not only referring to love but also to knowledge.